2006
DOI: 10.1212/01.wnl.0000249313.25627.2e
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiac 123 I-MIBG scintigraphy in idiopathic REM sleep behavior disorder

Abstract: Idiopathic REM sleep behavior disorder (RBD) may represent prodromal synucleinopathies. We report markedly reduced cardiac (123)I-metaiodobenzylguanidine uptake, consistent with the loss of sympathetic terminals, in idiopathic RBD. We also demonstrate that this reduction is of the same magnitude as that found in patients with Parkinson disease. The results are consistent with the hypothesis that idiopathic RBD in older patients is a forme fruste of Lewy body disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(161 citation statements)
references
References 7 publications
(14 reference statements)
11
146
0
4
Order By: Relevance
“…[1][2][3] Synucleinopathies were often associated with symptoms of autonomic dysfunction, such as impaired blood pressure control and reduced heart rate variability. 4,5 Consistently, individuals with idiopathic RBD experienced worse autonomic function, including cardiovascular, gastrointestinal, and urinary domains, relative to control participants. 6,7 The autonomic nervous system may have a role in the prepathologic state or contribute to the precipitating factors of the acute phase of stroke, such as atherosclerosis and sympathetic hyperactivity.…”
mentioning
confidence: 84%
“…[1][2][3] Synucleinopathies were often associated with symptoms of autonomic dysfunction, such as impaired blood pressure control and reduced heart rate variability. 4,5 Consistently, individuals with idiopathic RBD experienced worse autonomic function, including cardiovascular, gastrointestinal, and urinary domains, relative to control participants. 6,7 The autonomic nervous system may have a role in the prepathologic state or contribute to the precipitating factors of the acute phase of stroke, such as atherosclerosis and sympathetic hyperactivity.…”
mentioning
confidence: 84%
“…The 123I-MIBG studies showed markedly decreased cardiac uptake in PD, DLB and PAF, which is a common feature of Lewy body diseases (Courbon et al, 2003;Kashihara et al, 2006;Yoshita et al, 2006). We reported markedly reduced cardiac 123I-MIBG uptake in iRBD as well as in PD or DLB (Miyamoto et al, 2006;Miyamoto et al, 2008) (Figure 5). In our recent case report ), we described a small subset of iRBD patients who have relatively preserved uptake at RBD onset, but which then becomes lost over the follow-up period.…”
Section: I-mibg Scintigraphymentioning
confidence: 50%
“…Idiopathic RBD (iRBD), which develops in middle age or later and progresses chronically, in particular is a common clinical manifestation of Lewy body-related syndrome and is regarded as a clinical entity from pathological aspects. For example (Table 1), it has been elucidated that iRBD is often accompanied by soft motor signs, olfactory and color identification deficits, decreased cardiovascular and respiratory changes between REM and Non-REM sleep, reduced cardiac 123 I-metaiodobenzylguanidine (123I-MIBG) uptake, impairment of visual memory and visuo-spatial construction revealed by neuropsychological testing, EEG slowing during wakefulness or sleep, and decreased strial dopaminergic innervation and reduced pre-synaptic strial dopamine transporter binding on SPECT or positron emission topography (PET) scans, which are considered as non-motor symptoms of Parkinson's disease (PD) (Becker et al, 2002;Gagnon et al, 2006;Miyamoto et al, 2006;Miyamoto et al, 2008). Furthermore, despite the limited number of pathological reports on iRBD, the characteristics of iRBD have been supported to have a close relationship with Lewy body pathology .…”
Section: Introductionmentioning
confidence: 99%
“…REM behavior disorder (RBD) is a new pathological entity associated with PD. RBD patients present an evident myocardial noradrenergic denervation as demonstrated by cardiac sympathetic neuroimaging [21,22]. Most PD patients may eventually develop dementia.…”
Section: Sympathetic System In Parkinson's Diseasementioning
confidence: 99%